Assessing venous thromboembolism risk in lung cancer: a comprehensive evaluation of the khorana score, clinical characteristics, and incidence of thrombosis - Dougherty, Sean C.; Singh, Rishika; McKinney, Caleb; Singh, Aditya; Masur, Jack; Lynch, Alia C.; Gentzler, Ryan D.; Novicoff, Wendy; Roberts, Nathan; Hall, Richard D. (Frontiers in Oncology, 2026)
IntroductionVenous thromboembolism (VTE) occurrence in patients with lung cancer is associated with significant morbidity and mortality. The Khorana Score (KRS) is a validated risk stratification tool developed to estimate risk of VTE in patients with cancer that incorporates clinical and laboratory parameters to calculate individual risk. However, limitations of the KRS in lung cancer have been reported, and identification of other risk factors associated with increased risk of VTE are needed in this population.MethodsWe retrospectively evaluated 485 patients with advanced non-small cell lung cancer (NSCLC) and 67 patients with small cell lung cancer (SCLC) treated at our institution between March 2015 and April 2023 to assess the performance of the KRS in estimating risk of VTE in multiple clinically distinct subtypes of lung cancer.ResultsThe median patient age at diagnosis was 66 years (range, 30-94 years). Patients were predominantly male (51.1%), Caucasian (81%), and had a history of smoking (79.4%). VTE events were observed in 123 patients (22.3%); 51 patients had DVT (41.5%), 50 patients had PE (40.7%), 13 patients had concurrent DVT and PE (7.3%), and other VTE occurred in 9 patients (7.3%). 478 patients (86.6%) had low-risk KRS (score = 0-2) and 74 patients (13.4%) had high-risk KRS (score ≥3). No statistically significant difference in VTE incidence was observed based on baseline KRS. Clinical factors that were noted to be associated with increased risk of VTE were NSCLC histology, Black race, and the presence of an oncogenic driver mutation. No significant differences in overall survival were noted in patients that experienced VTE.DiscussionThis study highlights the limitations of the KRS in predicting risk of development of VTE in patients with NSCLC and SCLC and identifies multiple clinical parameters associated with increased risk of VTE. Development of further risk stratification tools incorporating these clinical factors in addition to those in the KRS should be considered.